2017
DOI: 10.1093/ajae/aax058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crop Insurance Premium Subsidies on Crop Acreage

Abstract: Crop insurance premium subsidies affect patterns of crop acreage for two reasons. First, holding insurance coverage constant, premium subsidies directly increase expected profit, which encourages more acreage of insured crops (direct profit effect). Second, premium subsidies encourage farms to increase crop insurance coverage. With more insurance coverage, farms obtain more subsidies, and farm revenue becomes less variable as indemnities offset revenue shortfalls, so acreage of insured crops likely increases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 34 publications
5
68
1
1
Order By: Relevance
“…Also, in a US national study, Yu et al . () have estimated an acreage response of 0.43% to a 10% change in crop insurance subsidy rates. Most of the additional land would be of low productivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, in a US national study, Yu et al . () have estimated an acreage response of 0.43% to a 10% change in crop insurance subsidy rates. Most of the additional land would be of low productivity.…”
Section: Discussionmentioning
confidence: 97%
“…For the Corn Belt region, Claassen et al (2017) found evidence that crop revenue insurance has slightly increased the conversion of non-cropland to cropland in addition to a somewhat larger effect on crop choices. Also, in a US national study, Yu et al (2017) have estimated an acreage response of 0.43% to a 10% change in crop insurance subsidy rates. Most of the additional land would be of low productivity.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few explicit discussions on how premium subsidies in crop insurance affect crop choice (e.g., Goodwin and Smith, ; Miao et al., ; Yu et al., ). The interaction between crop insurance and self‐insurance and its relationship with choice across crops remains to be fully characterized.…”
Section: Effects Of Crop Insurance On Farm Resource Allocationmentioning
confidence: 99%
“…Yu et al. () directly estimate the acreage effect of crop insurance premium subsidies. Goodwin and Smith () present preliminary empirical estimates indicating potential positive effect of premium subsidy.…”
mentioning
confidence: 99%
“…This form of domestic support tends to be trade distorting (Chau and de Gorter, ; Goodwin and Mishra, ; Key and Roberts, ; Latruffe and Le Mouël, ; O'Toole and Hennessy, ; Urban et al., ). While interest in the impact of commodity support on input use dates as far back as in Floyd () and has continued in recent times (Yu et al., ), to our knowledge, none of the extant literature has explored whether direct payments induce input‐ and output‐biased technical change in U.S. agriculture at the national level.…”
Section: Introductionmentioning
confidence: 99%